Self Compacting Green Concrete (SCGC) Kuat Awal Tinggi Menggunakan CaCO3, Carbide Waste, dan Bottom Ash. - Firdaus, Muhammad Zuhal; Sunaryoto, Achmad Firmansyah (AGREGAT, 2024)
The performance improvement can be done by applying innovative principles in construction projects because the most consumed product on earth besides water is concrete, more than 4 billion tons of carbon dioxide per year is produced from this industry. To reduce this problem, research on the utilization of alternative materials to replace cement in SCC (Self Compacting Concrete) in High Early Strength Concrete is one of the good solutions. Alternatively, using CaCO3 and Waste Calcium Carbide to reduce the amount of cement so that less carbon dioxide is produced and using Bottom Ash as a sand substitute to reduce the cost of fine aggregate. This research aims to obtain SCC concrete with a compressive strength of more than 15 MPa at the age of 1 day with a mixture of these environmentally friendly materials, with the chemical properties of environmentally friendly materials reacting simultaneously, this adds to the optimization of concrete innovations carried out both in terms of concrete compressive strength, environmentally friendly, and reduction of material waste. The results showed an increase in effectiveness in reducing the use of cement but proven of increasing the 1 day Compressive Strength and the effectiveness of carbon dioxide emissions generated by 26.58%.